We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.

+0

# Evaluate \$a^3 + \dfrac{1}{a^3}\$ if \$a+\dfrac{1}{a} = 6\$.

0
956
3

Evaluate \$a^3 + \dfrac{1}{a^3}\$ if \$a+\dfrac{1}{a} = 6\$.

Sep 28, 2017

### Best Answer

#3
+3

Evaluate   a^3  + 1/a^3    if   a   + 1/a  = 6

If   a   + 1/a   = 6     square both sides

(a^2 + 2  + 1/a^2)   = 36

a^2  + 1/a^2    =   34

Note   that         a^3  + 1/a^3    can be factored as a sum of cubes....so we have

a^3  + 1/a^3  =

( a  +  1/a)  ( a^2 -  1 +  1/a^2)

(6)  ( a^2 + 1/a^2  - 1 )

(6) ( 34 - 1)  =

6 *  33  =

198   Sep 29, 2017
edited by CPhill  Sep 29, 2017

### 3+0 Answers

#1
0

Solve for a:
a^3 + 1/a^3 = 6

Bring a^3 + 1/a^3 together using the common denominator a^3:
(a^6 + 1)/a^3 = 6

Multiply both sides by a^3:
a^6 + 1 = 6 a^3

Subtract 6 a^3 from both sides:
a^6 - 6 a^3 + 1 = 0

Substitute x = a^3:
x^2 - 6 x + 1 = 0

Subtract 1 from both sides:
x^2 - 6 x = -1

Add 9 to both sides:
x^2 - 6 x + 9 = 8

Write the left hand side as a square:
(x - 3)^2 = 8

Take the square root of both sides:
x - 3 = 2 sqrt(2) or x - 3 = -2 sqrt(2)

Add 3 to both sides:
x = 3 + 2 sqrt(2) or x - 3 = -2 sqrt(2)

Substitute back for x = a^3:
a^3 = 3 + 2 sqrt(2) or x - 3 = -2 sqrt(2)

Taking cube roots gives (3 + 2 sqrt(2))^(1/3) times the third roots of unity:
a = -(-3 - 2 sqrt(2))^(1/3) or a = (3 + 2 sqrt(2))^(1/3) or a = (-1)^(2/3) (3 + 2 sqrt(2))^(1/3) or x - 3 = -2 sqrt(2)

Add 3 to both sides:
a = -(-3 - 2 sqrt(2))^(1/3) or a = (3 + 2 sqrt(2))^(1/3) or a = (-1)^(2/3) (3 + 2 sqrt(2))^(1/3) or x = 3 - 2 sqrt(2)

Substitute back for x = a^3:
a = -(-3 - 2 sqrt(2))^(1/3) or a = (3 + 2 sqrt(2))^(1/3) or a = (-1)^(2/3) (3 + 2 sqrt(2))^(1/3) or a^3 = 3 - 2 sqrt(2)

Taking cube roots gives (3 - 2 sqrt(2))^(1/3) times the third roots of unity:
a = -(-3 - 2 sqrt(2))^(1/3)   or   a = (3 + 2 sqrt(2))^(1/3)   or   a = (-1)^(2/3) (3 + 2 sqrt(2))^(1/3)   or a = (3 - 2 sqrt(2))^(1/3)   or   a = (-1)^(2/3) (3 - 2 sqrt(2))^(1/3)   or   a = -(2 sqrt(2) - 3)^(1/3)

Sep 29, 2017
#2
0

Solve for a:
a + 1/a = 6

Bring a + 1/a together using the common denominator a:
(a^2 + 1)/a = 6

Multiply both sides by a:
a^2 + 1 = 6 a

Subtract 6 a from both sides:
a^2 - 6 a + 1 = 0

Subtract 1 from both sides:
a^2 - 6 a = -1

Add 9 to both sides:
a^2 - 6 a + 9 = 8

Write the left hand side as a square:
(a - 3)^2 = 8

Take the square root of both sides:
a - 3 = 2 sqrt(2) or a - 3 = -2 sqrt(2)

Add 3 to both sides:
a = 3 + 2 sqrt(2) or a - 3 = -2 sqrt(2)

Add 3 to both sides:
a = 3 + 2 sqrt(2)      or         a = 3 - 2 sqrt(2)

[3 +2 sqrt(2)]^3 + 1/ [3 + 2 sqrt(2)]^3 =198

Sep 29, 2017
#3
+3
Best Answer

Evaluate   a^3  + 1/a^3    if   a   + 1/a  = 6

If   a   + 1/a   = 6     square both sides

(a^2 + 2  + 1/a^2)   = 36

a^2  + 1/a^2    =   34

Note   that         a^3  + 1/a^3    can be factored as a sum of cubes....so we have

a^3  + 1/a^3  =

( a  +  1/a)  ( a^2 -  1 +  1/a^2)

(6)  ( a^2 + 1/a^2  - 1 )

(6) ( 34 - 1)  =

6 *  33  =

198   CPhill Sep 29, 2017
edited by CPhill  Sep 29, 2017